Hydrogen-bond acidity of ionic liquids: an extended scale1. Issue 29 (7th August 2015) - Kurnia, Kiki A.; Lima, Filipa; Cláudio, Ana Filipa M.; Coutinho, João A. P.; Freire, Mara G.
<x xml:space="preserve">Abstract</x> Through the combination of experimental and theoretical approaches, a new extended scale for the hydrogen-bonding acidity of ionic liquids is provided.